The Word on the Street: Architectural Criticism - Morgenthaler, Hans Rudolf (The Meaning of Modern Architecture, 2015)
The four previous chapters laid out a fertile methodical approach to the interpretation of Modernist architecture. The theories summarized in these chapters were proposed by artists, art historians, and psychologists. Was this new approach actually noticed anywhere in the world of architecture? Were the new theories also accepted by professional critics? And, did the architects themselves realize that they created and presented something new, something unfamiliar? A survey of the major art and architectural magazines and journals published in Germany and Austria will provide answers to these questions. In addition, this perusal will also provide a chronological account of the introduction of the new architecture and the new interpretative methods.